Mixing signals: Molecular turn ons and turn offs for innate γδ Τ cells - Bekiaris, Vasileios; Šedý, John S.; Ware, Carl F. (Frontiers in Immunology, 2014)
Lymphocytes of the gamma delta (γδ) T cell lineage are evolutionary conserved and although they express rearranged antigen-specific receptors a large proportion respond as innate effectors. γδ T cells are poised to combat infection by responding rapidly to cytokine stimuli similar to innate lymphoid cells. This potential to initiate strong inflammatory responses necessitates inhibitory signals are balanced with activation signals. Here, we discuss some of the key mechanisms that regulate the development, activation and inhibition of innate γδ T cells in light of recent evidence that the inhibitory Ig-superfamily member B and T lymphocyte attenuator (BTLA) restricts their differentiation and effector function.